The efficacy of the verbal behaviour of volleyball coaches during competition - M. P. Moreno; J. A. Santos; L. A. Ramos; E. Cervelló; D. Iglesias; F. Del Villar (Asociación Española de Ciencias del Deporte, 2010)
The study we present here, which concentrates on analysing the efficacy of the verbal behaviour of coaches, aims to define an intervention protocol for volleyball coaches during competition. The research was carried out by means of a questionnaire given to 25 volleyball experts (university volleyball teachers and volleyball coaches with experience at top national level). The variables analysed consist of the study of the content of the information transmitted by the coaches, in accordance with each moment of the game in which communication with the players occurs. As for the results obtained, and taking into account that there are differences between the different moments of the game, it should be stressed that the overall information must be mainly tactical and refer to both the opponents and one's own team in equal measure. It must be positive and should not include more than three pieces of information. KEY WORDS: information to the player, team management, coach training, volleyball.